Interlaced, modular, distributive and boolean bilattices - Movsisyan, Yu. M. (Armenian Journal of Mathematics, 2008)
We will discuss the concepts of interlaced, modular, distributive, Boolean (DeMorgan) and Ginsberg bilattices with their characterizations by hyperidentities and superproducts.